Tailor Training Strategy for Persons with Disabilities at UPTD Bina Karya Workshop, South Bengkulu Manna Regency - Citra Dwi Palenti; Ririn Gusti; Dwi Ismawati; Afrizah Widhea; Ari Putra (Universitas Negeri Padang, 2023)
The aim of this study is to describe the sewing training for people with disabilities at the UPTD Loka Bina Karya Manna, South Bengkulu Regency. This study utilized a qualitative descriptive method. The findings indicate that the participants who attended the training were able to acquire sewing skills. The learning materials used in the training include introduction to sewing machines from the sewing machine knowledge module, basic pattern-making from the fashion pattern-making module, various stitches from the fabric knowledge and basic stitches module, and simple sewing process from the simple sewing process module. The learning tools provided were pins, hand needles for hand sewing, and machine needles for using the sewing machines and overlock machines. The learning approach focused on skill empowerment, while the learning strategy used direct teaching, beginning from stating the training objectives, providing explanations of the materials by the instructor in front of the class, and ending with question and answer sessions. The training evaluation utilized a summative evaluation method.